2009
DOI: 10.1159/000226284
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Mammography and Ultrasound in the Evaluation of Male Breast Disease: A New Algorithm

Abstract: Background: The purpose of this study was to define the diagnostic accuracy of mammography and ultrasound in the evaluation of male breast disease, and to suggest a diagnostic protocol for male breast disease. Material and Methods: We retrospectively reviewed clinical, radiographic, and pathologic records of 75 patients. Breast Imaging Reporting and Data System (BI-RADS) category 4–5 mammograms and ultrasonograms were suggested as suspicious for malignancy. Results: Of the 75 patients, 23 (31%) were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
2
12
1
1
Order By: Relevance
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammography is now an important tool for the detection of early stages of breast cancer (Smith et al, 2003;Adibelli et al, 2009) and thus has a large influence on breast cancer stage at presentation (Dalton et al, 2006;Masi et al, 2007;Pasick et al, 2008). Previous studies have found that the implementation rate of mammography is closely related to income level: people with lower incomes have lower mammography implementation rate (Ward et al, 2008;Cunningham et al, 2009), which suggests that these patients have a higher risk of presentation with a larger, more advanced stage tumor.…”
Section: Discussionmentioning
confidence: 99%
“…A number of variables have been reported to affect prognosis in male breast cancer including tumor stage (1) and axillary node status (16). Borgen and colleagues retrospectively reviewed 104 male breast cancers and showed that on multivariate analysis, the most powerful predictor of outcome in men was the status of axillary lymph nodes, and the only prognostic factor that added significantly to this predictive power was the duration of symptoms (17).…”
Section: To the Editormentioning
confidence: 99%
“…(4)(5)(6) Breast ultrasonography is also useful for evaluating male patients who present with breast masses and nipple discharge, or when the mammographic findings are not characteristic of gynaecomastia. (5,6) Mammographic or breast ultrasonographic primary findings of a unilateral and discrete mass in a male breast, at an eccentric location with respect to the nipple-areolar complex, should always raise the suspicion of a breast carcinoma. (3,7,8) This is particularly true for a solid or complex cystic breast mass that demonstrates spiculated, angulated or microlobulated margins, and increased vascularity.…”
Section: Discussionmentioning
confidence: 99%